SANKSI TINDAK PIDANA PEMERKOSAAN OLEH ANAK DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Janah, Kharisatul (Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research is entitled about the Criminal Act of Child Rape in the Perspective of Islamic Criminal Law. Two things are raised as the focus of the research, How is the criminal sanction of child rape according to positive law. How is the Perspective of Islamic Criminal Law on the Penalty of Child Rape. The method used for this research uses a library research approach. Sources of data used: library data sources consisting of primary, secondary and tertiary legal materials. Legal materials in obtaining data, such as al-Qur'an al-Hadith, laws and books related to the object of research. Secondary legal materials: data sources that provide explanations for primary data: magazines, and other data relating to the object of research. tertiary legal materials: additional data sources that provide explanations for secondary data. The data analysis technique is to classify existing data, namely primary, secondary and tertiary data. After the data is classified, the writer tries to analyze primary, secondary and tertiary data. Then after being analyzed, the writer tries to conclude. From the results of this study, the researcher can conclude that the sanctions that can be imposed are: imprisonment, a maximum of ½ (one half) of the maximum imprisonment for adults. Article 81 paragraph.6 of the Law on Juvenile Justice System states that if a criminal act committed by a child is a criminal act which is punishable by death or life imprisonment, then the punishment imposed on the child: imprisonment for a maximum of 10 (ten years). . The criminal sanction for the perpetrator of rape by a child according to Islamic criminal law, if the child is aged, the punishment that can be received is the same as the punishment for hadd zina, the scholars have agreed to enforce hadd for the perpetrator of rape if there is evidence that obliges him to haved or the perpetrator confesses his actions. If it does not fulfill this, then the ta'zir court will be applied. If the child has not reached puberty, then he must pay a fine that is taken from his parents' property Keywords: Islamic Criminal Law, Rape, Children